Extension Educators’ Use of Social Media for Promoting Extension-related Activities - Enoch Teye Kwao Ametepey; Jeff Miller; Casandra Cox; George Wardlow (Journal of Applied Communications, 2025)
The insurgence of the internet and digital media usage has changed the landscape for information acquisition across disciplines globally. The integration of social media in Extension education has altered communication strategies among educators, farmers, and various stakeholders. This research investigates the degree to which Extension educators in Arkansas utilize social media for professional purposes, identifies demographic factors influencing usage, and analyzes the challenges related to its adoption. This study, informed by the Uses and Gratifications Theory (UGT), utilized a cross-sectional survey design to gather data from 97 Extension educators in three districts. Findings indicate social media is primarily used for event announcements, program marketing, and educational information dissemination, yet it remains underused for interactive and evaluative functions, including client collaboration and program impact assessment. Furthermore, the results demonstrate notable variations in social media adoption among job roles, with 4-H & Youth Development agents showing the highest levels of usage. Also, female agents engage with social media more often than male educators. Significant challenges encompass restricted time for content development and training, absence of incentives, and complexities in navigating social media platforms. Extension educators acknowledge the potential of social media for outreach and engagement, despite existing barriers. The research suggests implementing targeted training, providing specialized administrative support, and improving policies to enhance the effectiveness of social media in Extension education. Future research should investigate optimum practices and training requirements to improve educators’ social media utilization.
Keywords: Social media; extension education; 4-H and Youth Development; family and consumer science; Uses and Gratification; agricultural communications; digital engagement